(untitled) - Krzyzak, Adam; Vision Interface '88 Conference (Singapore, 1989)
"Composed of selected and expanded papers presented at the Vision Interface '88 Conference in Edmonton, Alberta, Canada, June 6-10, 1988"--Frwd.; This is an up-to-date volume of selected and expanded papers originating from Vision Interface 88, a conference held in Edmonton, Canada. A broad range of topics are covered-from image processing to hardware design. They include robot vision, biomedical imaging, remote sensing and parallel processing, shape recognition and features, computational methods in vision, and three dimensional vision and application
Keywords: Computer vision -- Congresses; Pattern recognition systems -- Congresses.; Hệ thống nhận dạng mẫu -- Hội thảo